La trompeta del cisne - White, E. B. (Elwyn Brooks), 1899-1985; Frascino, Edward (Barcelona : Noguer y Caralt editores, 2001)
Knowing how to read and write is not enough for Louis, a voiceless Trumpeter swan; his determination to learn to play a stolen trumpet takes him far from his wilderness home.
Translation of: The trumpet of the swan.
Accelerated Reader
Keywords: Trumpeter swan -- Juvenile fiction; Swans -- Juvenile fiction; Cisne trompeta -- Novela juvenil; Cisnes -- Novela juvenil